The Effect of Work Competence and Availability of Facilities on Employee Performance with Supervision as a Moderating Variable at the Sleman Regency DPMPTSP - Virawan, Nanang; Sutirman (Indonesian Journal of Advanced Research, 2026)
This study aims to examine the effect of competence and facility availability on employee performance at the DPMPTS Kabupaten Sleman, with supervision as a moderating variable. This is a quantitative study using SEM-PLS. The results of the study indicate that work competence has a positive and significant effect on employee performance, facility availability has a positive and significant effect on employee performance, supervision has a positive and significant effect on work competence, supervision has a positive and significant effect on the availability of facilities, supervision has a negative and insignificant effect on employee performance, supervision as a moderator variable has a negative and insignificant effect in moderating the effect of work competence on employee performance, and supervision as a moderator variable has a positive and insignificant effect in moderating the effect of the availability of facilities on employee performance.